Ryanodine-induced vasoconstriction of the gerbil spiral modiolar artery depends on the Ca2+ sensitivity but not on Ca2+ sparks or BK channels - Krishnamoorthy, Gayathri; Reimann, Katrin; Wangemann, Antje Philine (My University, 2016)
Background In many vascular smooth muscle cells (SMCs), ryanodine receptor-mediated Ca2+ sparks activate large-conductance Ca2+-activated K+ (BK) channels leading to lowered SMC [Ca2+]i and vasodilation. Here we investigated whether Ca2+ sparks regulate SMC global [Ca2+]i and diameter in the spiral modiolar artery (SMA) by activating BK channels. Methods SMAs were isolated from adult female gerbils, loaded with the Ca2+-sensitive flourescent dye fluo-4 and pressurized using a concentric double-pipette system. Ca2+ signals and vascular diameter changes were recorded using a laser-scanning confocal imaging system. Effects of various pharmacological agents on Ca2+ signals and vascular diameter were analyzed. Results Ca2+ sparks and waves were observed in pressurized SMAs. Inhibition of Ca2+ sparks with ryanodine increased global Ca2+ and constricted SMA at 40 cmH2O but inhibition of Ca2+ sparks with tetracaine or inhibition of BK channels with iberiotoxin at 40 cmH2O did not produce a similar effect. The ryanodine-induced vasoconstriction observed at 40 cmH2O was abolished at 60 cmH2O, consistent with a greater Ca2+-sensitivity of constriction at 40 cmH2O than at 60 cmH2O. When the Ca2+-sensitivity of the SMA was increased by prior application of 1 nM endothelin-1, ryanodine induced a robust vasoconstriction at 60 cmH2O. Conclusions The results suggest that Ca2+ sparks, while present, do not regulate vascular diameter in the SMA by activating BK channels and that the regulation of vascular diameter in the SMA is determined by the Ca2+-sensitivity of constriction.
Citation: Krishnamoorthy, G., Reimann, K. & Wangemann, P. BMC Physiol (2016) 16: 6. https://doi.org/10.1186/s12899-016-0026-z
Keywords: Ca2+ spark; Ca2+ sensitivity; Spiral modiolar artery; Ryanodine; Vascular diameter; BK channels